2011
DOI: 10.1097/pas.0b013e31820f1ce0
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial Primitive Neuroectodermal Tumors of the Central Nervous System in Adults

Abstract: Advances in understanding the molecular basis of primitive neuroectodermal tumors of the central nervous system (CNS-PNET) biology are critical to improve patient outcome. Recently, new data on their molecular features have been reported, suggesting that supratentorial PNET (s-PNET) in adult patients may represent a specific tumor entity among CNS-PNETs. In this study, we analyzed the clinicopathologic and molecular features of 12 cases of s-PNET in adult patients. The follow-up analysis showed that these tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
12
0
3
Order By: Relevance
“…Furthermore, Gessi et al . have shown that a high incidence of TP53 mutations and the absence of amplification of the c-myc/N-myc genes in adult sPNET, in comparison to pediatric PNET, suggest that adult sPNET should be an independent subset of tumors among CNS-PNETs [3]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Gessi et al . have shown that a high incidence of TP53 mutations and the absence of amplification of the c-myc/N-myc genes in adult sPNET, in comparison to pediatric PNET, suggest that adult sPNET should be an independent subset of tumors among CNS-PNETs [3]. …”
Section: Discussionmentioning
confidence: 99%
“…On magnetic resonance imaging (MRI), these tumors appear as well-delimited, inhomogeneous, and variably contrast-enhanced lesions. Furthermore, on T1-weighted images, PNETs appear hypointense, and on T2-weighted images they appear hyperintense [3-6]. …”
Section: Introductionmentioning
confidence: 99%
“…Primitive neuroectodermal tumor (PNET)/Ewing Sarcoma (ES) is a rare family of malignancies in the CNS, always creating diagnostic challenges in CNS tumors . Unlike the central type PNET, which accounts for about 2.5% of brain tumors in children and about 0.46% in adults, the ES/pPNET in CNS also occurs with intracranial/intraspinal meningeal extension, characterized by fusion of the EWSR1 gene (22q12) with a member of the ETS gene family, including FLI1, ERG, ETV1, EIAF and so on, showing different histogenesis, molecular characteristics, and better clinical prognosis . The ES/pPNET is rather uncommon in the CNS and we could only identify four cases in the archives of our department over 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unlike the central type PNET, which accounts for about 2.5% of brain tumors in children and about 0.46% in adults, the ES/pPNET in CNS also occurs with intracranial/intraspinal meningeal extension, characterized by fusion of the EWSR1 gene (22q12) with a member of the ETS gene family, including FLI1, ERG, ETV1, EIAF and so on, showing different histogenesis, molecular characteristics, and better clinical prognosis. 2,[4][5][6][7][8][9]14,[23][24][25] The ES/pPNET is rather uncommon in the CNS and we could only identify four cases in the archives of our department over 6 years. Therefore, it is important to investigate the clinical pathological features and its possible differential diagnosis for the selection of proper therapy and accurate assessment of its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…They commonly occur in low grade gliomas and secondary GBMs, rarely in primary GBMs. IDH1 mutation have been observed also in a small percentage of adult PNETs (15)(16)(17). The PNET components are explained by two main hypotheses (8): PNET-like foci arise from pre-existing gliomas, most often a secondary GBM (neuroblastic or neuronal metaplasia) and the clonal expansion of tumour stem cells or progenitor cells resulting in PNET-like nodules (7,15,18).…”
Section: Therapeutic Approach In Glioblastoma Multiforme With Primitimentioning
confidence: 99%